Nitric oxide: A core signaling molecule under elevated GHGs (CO2, CH4, N2O, O3)-mediated abiotic stress in plants - Kabange, Nkulu Rolly; Mun, Bong-Gyu; Lee, So-Myeong; Kwon, Youngho; Lee, Dasol; Lee, Geun-Mo; Yun, Byung-Wook; Lee, Jong-Hee (Frontiers in Plant Science, 2022)
Nitric oxide (NO), an ancient molecule with multiple roles in plants, has gained momentum and continues to govern plant biosciences-related research. NO, known to be involved in diverse physiological and biological processes, is a central molecule mediating cellular redox homeostasis under abiotic and biotic stresses. NO signaling interacts with various signaling networks to govern the adaptive response mechanism towards stress tolerance. Although diverging views question the role of plants in the current greenhouse gases (GHGs) budget, it is widely accepted that plants contribute, in one way or another, to the release of GHGs (carbon dioxide (CO2), methane (CH4), nitrous oxide (N2O) and ozone (O3)) to the atmosphere, with CH4 and N2O being the most abundant, and occur simultaneously. Studies support that elevated concentrations of GHGs trigger similar signaling pathways to that observed in commonly studied abiotic stresses. In the process, NO plays a forefront role, in which the nitrogen metabolism is tightly related. Regardless of their beneficial roles in plants at a certain level of accumulation, high concentrations of CO2, CH4, and N2O-mediating stress in plants exacerbate the production of reactive oxygen (ROS) and nitrogen (RNS) species. This review assesses and discusses the current knowledge of NO signaling and its interaction with other signaling pathways, here focusing on the reported calcium (Ca2+) and hormonal signaling, under elevated GHGs along with the associated mechanisms underlying GHGs-induced stress in plants.